Biochemical characterisation of alpha-amylase inhibitors from achyranthes aspera and their interactions with digestive amylases of coleopteran and lepidopteran insects - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Giri, Ashok P.; Chhabda, Pavan J.; Kachole, Andmanvendra S. (Journal of the Science of Food and Agriculture, 2011)
BACKGROUND: Starchy seeds are an important food and a source of dietary ingredients in many countries. However, they suffer from extensive predation by bruchids (weevils) and other pests. alpha-Amylase inhibitors are attractive candidates for the control of seed weevils, as these insects are highly dependent on starch as an energy source. RESULTS: A proteinaceous alpha-amylase inhibitor from the seeds of Achyranthes aspera was identified, purified and characterised. In electrophoretic analysis, two prominent amylase inhibitor activity bands (AI1 and AI2) were detected. The inhibitor was purified 9.99-fold with 1206.95 total amylase inhibitor units mg(-1) protein. The molecular weight of the purified inhibitor was around 6 kDa. The isolated alpha-amylase inhibitor was found to be resistant to heat and proteolysis. Feeding analysis of Callosobruchus maculatus larvae on a diet containing seed powder of A. aspera revealed that survival of the larvae was severely affected, with the highest mortality rate occurring on the fifth day of feeding. The isolated inhibitor inhibited the majority of amylase isoforms of C. maculatus, Tribolium confusum and Helicoverpa armigera in electrophoretic analysis and solution assays. CONCLUSION: The information obtained in the present investigation could be useful for a genetic engineering approach that would make seeds resistant to storage pest infestations. (C) 2011 Society of Chemical Industry
Keywords: Achyranthes aspera; Amylase inhibitors; amylases; Callosobruchus maculatus; Tribolium confusum